The Christian-Muslim frontier : a zone of contact, conflict, or cooperation - Apostolov, Mario (London ; New York : RoutledgeCurzon, 2004)
An examination of the civilisational interface between Christianity and Islam from the unique perspective as a zone of contact rather than a distinct boundary.
Book Cover; Title; Copyright; Contents; Introduction; 1 The concept of the Christian-Muslim frontier as a zone of contact; 2 The history of the Christian-Muslim frontier; 3 Modern nation states and the frontier; 4 Interspersing communities and the postmodern functional frontier; 5 Geopolitics of the frontier; 6 The Christian-Muslim frontier as a psychological phenomenon; 7 The international security dimension of the frontier; 8 The economic dimension of the frontier; Conclusion; Bibliography; Index.
Includes bibliographical references (pages 186-194) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; International relations; Security, International; Islam -- Relations -- Christianisme; Christianisme -- Relations -- Islam; Relations internationales; international relations; 11.07 relations between religions; POLITICAL SCIENCE -- Globalization; Christianity; Interfaith relations; International relations; Islam; Security, International; Christentum; Islam; Islam; Christendom; Interreligieuze dialoog